1990
DOI: 10.1001/jama.1990.03450010067032
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplantation Under FK 506

Abstract: The experimental immunosuppressive drug FK 506 was given to 36 renal transplant recipients, many of whom were highly sensitized. Ten were undergoing kidney retransplantation, 10 also underwent liver transplantation at an earlier time (6 patients) or concomitantly (4 patients), and 2 patients received a third organ (heart or pancreas) in addition to a liver and kidney. With follow-ups of 4 to 13 months, all but 2 of the 36 patients are alive, 29 (81 %) are dialysis 'free, and most have good renal function. Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
1
5

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(84 citation statements)
references
References 21 publications
0
78
1
5
Order By: Relevance
“…[1][2][3][4] The use of this agent in the pediatric population is less well described. We and others have previously reported that its use in pediatric patients is associated with excellent patient and graft survival results in a relatively small number of patients.…”
mentioning
confidence: 99%
“…[1][2][3][4] The use of this agent in the pediatric population is less well described. We and others have previously reported that its use in pediatric patients is associated with excellent patient and graft survival results in a relatively small number of patients.…”
mentioning
confidence: 99%
“…[10][11][12] It had been learned that the three major side effects of the drug (nephrotoxicity, neurotoxicity, and diabetogenicity) were comparable to cyclosporine. Hypertension and hyperlipidemia were less than in historical cyclosporine controls, and the cosmetic effects of cyclosporine (hirsutism, gingival hyperplasia, and facial brutalization) had not been seen.…”
Section: Pilot Primary Treatment Experiencementioning
confidence: 99%
“…12,35,36 A randomized renal transplantation trial of tacrolimus versus cyclosporine was carried out in Pittsburgh in 1990 and 1991 37 but was suspended less than a year after its inception at the recommendation of the same Patients' Rights Committee that had taken similar action with the liver trial (see earlier).…”
Section: Kidney and Other Organ Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has well described in vitro and experimental in vivo immunosuppressive properties 1 , and has been used in clinical heart 2 , lungs 3 , liver 4 , kidney [5][6][7][8][9] , intestinal 10 , and islet 11 transplantation. The initial experiences in pediatric kidney transplantation have been previously described.…”
Section: Introductionmentioning
confidence: 99%